Criminal justice in the United States and Germany: history, modernization, and reform = Strafrecht in den Vereinigten Staaten und Deutschland - Berg, Manfred (Publikationen der Bayerischen Amerika-Akademie, 2006)
Criminal justice is a salient and controversial political issue in both Germany and the United States. Public perception is often dominated by media sensationalism and dramatized images of popular culture, while experts tend to focus on institutions and procedures. This volume brings together contributions from German and American scholars representing various disciplines, including criminology, criminal law, political science, sociology, and history. The essays address both broader social issues, such as race, gender, and the death penalty, and specific problems of administering criminal justice, including sentencing, corrections, or electronic monitoring. Their unifying themes are the dynamics of legal and social change and the quest for reform to make the criminal justice system both fairer and more efficient. Some of the essays invoke a comparative perspective, while others focus on national case studies
Beitr. teilw. dt., teilw. engl
Keywords: Aufsatzsammlung; USA; Rechtsvergleich; Strafrecht; Deutschland